Sensing religion, observing religion, reconstructing religion: Contingency and pluralization in post-Westphalian context - Beyer, Peter (Social compass, 2016)
The article argues that what is performed and understood as religion in global society has in the course of the modern centuries come to be increasingly dominated by the idea that religion is something distinct and differentiated, something distinct from what is not religion, namely the secular. It manifests itself principally as a plurality of identified and performed religions. Towards the latter half of the 20th century, however, that dominant understanding of religion has come to be increasingly challenged by alternative ways of ‘sensing religion’, alternative ways that are to some extent a reflection of new developments in this domain of religion in global society. They are also indicative of a reassessment of alternative ways of understanding and doing religion that have always accompanied the dominant sense. This reassessment allows the ‘hidden’ and ‘ignored’ to appear as religion and be recognized as such without negating the hitherto dominant form. The first of these developments is analyzed as the construction of a Westphalian system for religion; the reassessment and transformation is discussed under the contrasting idea of a post-Westphalian circumstance.